A study on the preference of the UPV social science student between violence and non-violence as a progress on change in the Philippine scociety. - Berlin, Sharon Joy
The study was conducted among 100 students of the Division of Social SCiences, University of the Philippines in the Visayas City. It attempted to answer the following questions: 1. Violence and Non-violence: which would the students prefer in changing society? 2. Is their preference related to some observable factors like sex, religiousity and family income? 3. What is the attitude of students towards the present government?, The respondents were almost unanimous (94 ) in their belief that Philippine society needs social changes. Moreover, they perceived the `monopoly of power by the few' as the primary problem of the nation. In the question of political preferences between the different methods of social transformation a considerable number (59 ) preferred the use of both violent and non-violent conduct in effecting changes. When factors like sex, religiousity and family income, were subjected to Chi-Square test, the result is as follows: 1. Female students were not politically less violent than their male counterparts. 2. The more religious the student the less likely he is violent. 3. High family income do not necessarily produce a preference on non-violent method. As to the third question, "What is the attitude of students towards the present Government?", there was a high (91 ) percentage that the present government works for the service of the few. A moderate number (52 ) believed that the government can not solve the country's problem, but in terms of the national leadership, a considerable number (61) categorized it as fairly responsive.